Workshop Peningkatan Kemampuan Praktik Penelitian Tindakan Kelas (PTK) bagi Guru Sekolah Dasar di Kota Pekanbaru - Marhadi, Hendri; Erlisnawati, Erlisnawati; Risma, Devi; Donal, Donal; Mardes, Siska; Mastuinda, Mastuinda; Nur, Raudha; Cindy, Vista; Samsinar, Samsinar; Syahfrika, Elvina; Khumaira, Raissa; Anjani, Sasta; Adila, Islahul (Jurnal SOLMA, 2025)
Background: Classroom Action Research is a research conducted in the classroom by teachers to determine the effect of the actions applied to a research subject in the classroom. CAR allows teachers to actively involve themselves in the development of learning, broadcast the teaching methods used, and find appropriate solutions to improve the effectiveness of student learning. However, in its implementation, many teachers still have low abilities in conducting classroom action research. Method: The research method used in several stages, namely FGD, training and mentoring and evaluation of training carried out at SD Negeri 147 Pekanbaru. Results: The results of the implementation of community service showed a significant increase in the ability of CARK teachers, with an N-gain of 0.71 in the high category. With this community service, it can be concluded that there was an increase in the skills carried out by Elementary School CARK teachers in Pekanbaru City. Conclusion: This activity successfully improved the PTK practical skills of elementary school teachers in Pekanbaru City, which ultimately had an impact on improving the quality of classroom learning and teacher professionalism.